A follow-up survey on the reproductive intentions and experiences of women undergoing planned oocyte cryopreservation. Issue 2 (February 2020) - Wafi, Ahmed; Nekkebroeck, Julie; Blockeel, Christophe; De Munck, Neelke; Tournaye, Herman; De Vos, Michel
Abstract: Research question: What are the current reproductive attitudes and experiences of women who have previously undergone planned oocyte cryopreservation (OoC)? Design: Retrospective questionnaire-based cohort study involving women who had previously undergone planned OoC between January 2009 and September 2016 at a single centre. Eligible women were contacted via e-mail and invited to complete an anonymous standardized questionnaire that had been developed to evaluate their current relationship status and reproductive situation, their attitudes towards planned OoC and their future reproductive intentions. Results: Of 460 women who had completed at least one OoC cycle, questionnaires were obtained from 138 women. After a mean (± SD) follow-up of 4.5 ± 2.4 years, two-thirds of respondents (65%) anticipated using their oocytes at some point in the future. The respondents reported an overwhelmingly positive attitude towards planned OoC, with 98% indicating they would recommend this intervention to others. Overall, 83% of respondents were single at the time they requested OoC but only 44% were single at the time they completed the survey. While 43/62 (69%) of women became pregnant after undergoing OoC, the majority 30/43 (70%) of these pregnancies were achieved without using their vitrified oocytes. Finally, 13/28 (46%) who used their cryopreserved oocytes stated that they had achieved a live birth. Conclusions: The majority of women who undergo OoC do not regret their experience and many have found a partner in subsequent years. Twenty-one per cent of respondents who attempted to conceive after OoC had a live birth using their cryopreserved oocytes.